Evaluation of the New Digital Goldmann Applanation Tonometer for Measuring Intraocular Pressure. (10th July 2014) - Sakaue, Yuta; Ueda, Jun; Seki, Masaaki; Tanaka, Takayuki; Togano, Tetsuya; Yoshino, Takaiko; Fukuchi, Takeo
Abstract : Purpose . To compare a new digital Goldmann applanation tonometer (dGAT) that measures intraocular pressure (IOP) in 0.1 mmHg increments to a standard Goldmann applanation tonometer (sGAT). Methods . This study included 116 eyes of 60 subjects. A single examiner first measured IOP in triplicate using either sGAT or dGAT, which was randomly chosen. After a 5-minute interval, the next set of three consecutive IOP was measured using the other GAT. Results . The mean IOP measured with sGAT was 16.27 ± 6.68 mmHg and 16.35 ± 6.69 mmHg with dGAT. Pearson's correlation coefficient was 0.998 (P < 0.01 ). The subjects were divided into three groups based on the mean IOP: IOP < 14 mmHg, 14–20 mmHg, or >20 mmHg. The Pearson's correlation coefficient within each group was 0.935, 0.972, and 0.997 (P < 0.01 ), respectively. The difference within the three consecutive IOP measurements (maximum–minimum) for dGAT (0.72 ± 0.34 mmHg) was significantly smaller than those with sGAT (0.92 ± 0.42 mmHg, P < 0.01 ). Even in patients with equal IOP (zero left-right difference) with sGAT (n = 30 ), dGAT detected IOP differences between the left and right eyes (0.47 ± 0.31 mmHg). Conclusion . Compared to sGAT, dGAT measurements are highly reproducible and less variable.